Embedded 5(4) pair trigonometrically-fitted Two Derivative Runge- Kutta method with FSAL property for numerical solution of oscillatory problems - Senu, Norazak; Ahmad, Nur Amirah; Ismail, Fudziah; Bachok @ Lati, Norfifah (World Scientific and Engineering Academy and Society (W S E A S), 2017)
Based on First Same As Last (FSAL) technique, an embedded trigonometrically-fitted Two Derivative Runge-Kutta method (TDRK) for the numerical solution of first order Initial Value Problems (IVPs) is developed. Using the trigonometrically-fitting technique, an embedded 5(4) pair explicit fifth-order TDRK method with a “small” principal local truncation error coefficient is derived. The numerical experiments are carried out and showed that our new method is more accurate and efficient when compared with other existing Runge-Kutta (RK) and TDRK methods of the same order.